The role of pH on Cr(VI) partitioning and isotopic fractionation during its incorporation in calcite. (15th November 2019) - Füger, A.; Bruggmann, S.; Frei, R.; Leis, A.; Dietzel, M.; Mavromatis, V.
Abstract: The Cr(VI) incorporation and chromium stable isotope composition in calcite has been studied in experiments performed in the pH range between 8.0 and 10.6 at constant temperature (T = 25 ± 1 °C), precipitation rate (rp  = 10 −7.7 ± 0.2 mol m −2  s −1 ) and total aqueous Cr(VI) concentration (Cr(VI) = 49.6 ± 1.3 mM). The obtained results indicate that Cr(VI) incorporation in calcite is pH-dependent and it is likely significantly affected by the formation of the aqueous CaCrO4 0 species. The experimental findings suggest that during calcite growth at pH < 9.4 Cr(VI) uptake in the solid phase is likely controlled by the initial adsorption and subsequent incorporation of CaCrO4 0 complexes, whereas this process is balanced by the additional uptake of aqueous CrO4 2− species when calcite forms at pH ≥ 9.4. This distinct mechanism of Cr(VI) incorporation into calcite is further confirmed by the Cr(VI) isotope fractionation between calcite and the precipitating solution. Owing to the longer CrO bond lengths in aqueous CaCrO4 0 compared to CrO4 2− species the lighter 52 Cr(VI) isotope is preferentially abundant in the aqueous CaCrO4 0 . The preferential uptake of the isotopically lighter CaCrO4 0 in the growing calcite results in Cr(VI) isotope fractionation, Δ 53 Crcalcite-solution  = δ 53 Cr calcite – δ 53 Crsolution, as low as −0.7‰ at pH 8. In contrast, at pH > 9.4 the smaller contributions of CaCrO4 0 in the total concentration of Cr(VI) in calcite yields in a Δ 53 Crcalcite-solution value close to 0‰. Our results imply that the chromium isotope tracer system applied to calcite, as an environmental proxy for the reconstruction of ocean redox conditions, is not solely a mirror of redox effects in the aqueous fluid from which the carbonates precipitate, but additionally is controlled by the pH of the forming fluid and consequently by the relative stability and the distribution of aquo-complexes. Speciation calculations for calcite precipitated from seawater and include the presence of CaCrO 0 complex, predict isotope fractionation values that lay within −0.67‰ < Δ 53 Crcalcite-solution  < −0.43‰, and come in excellent agreement with the experimental results of this study at similar pH conditions. This theoretical model predicts that calcite formation under pH conditions below 8.5 results in depletion of 53 Cr(VI) in the growing calcite crystal. In contrast, the Cr(VI) isotopic composition of precipitating calcite in alkaline solutions can be reasonably ascribed to directly depict the Cr(VI) isotopic signature of the aqueous solution from which calcite forms, at least within the range of the experimental conditions.